The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-03636-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired nanocoatings for biofouling prevention by photocatalytic redox reactions

Abstract: Aquaculture is a billion dollar industry and biofouling of aquaculture installations has heavy economic penalties. The natural antifouling (AF) defence mechanism of some seaweed that inhibits biofouling by production of reactive oxygen species (ROS) inspired us to mimic this process by fabricating ZnO photocatalytic nanocoating. AF activity of fishing nets modified with ZnO nanocoating was compared with uncoated nets (control) and nets painted with copper-based AF paint. One month experiment in tropical waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…Our results suggested that morphology and size affect the toxic potential of the nanostructure tested, with ZnO nanorods (NRG and NRS) being the least toxic among all of the tested nanostructures. Thus, our data support the hypothesis that supported ZnO nanorods can be used as a more environmentally friendly antifouling solution (Sathe et al 2017). Previously, it was shown that size, morphology, concentration, and bioavailability of nanostructures affect their toxicity (Ann et al 2015;Juganson et al 2015;Gonçalves et al 2018).…”
Section: Toxicity Of Zno Nanostructuressupporting
confidence: 88%
See 3 more Smart Citations
“…Our results suggested that morphology and size affect the toxic potential of the nanostructure tested, with ZnO nanorods (NRG and NRS) being the least toxic among all of the tested nanostructures. Thus, our data support the hypothesis that supported ZnO nanorods can be used as a more environmentally friendly antifouling solution (Sathe et al 2017). Previously, it was shown that size, morphology, concentration, and bioavailability of nanostructures affect their toxicity (Ann et al 2015;Juganson et al 2015;Gonçalves et al 2018).…”
Section: Toxicity Of Zno Nanostructuressupporting
confidence: 88%
“…Although there are large numbers of studies about toxicity of ZnONPs (Reddy et al 2007), there are no data about toxicity of ZnO nanorods with respect to different aquatic organisms belonging to different trophic levels. Because the use of supported ZnO nanorods (ZnONRG) has been proposed for the prevention of marine biofouling (Al-Fori et al 2014;Sathe et al 2017), we have attempted to compare the toxicity of ZnONPs, ZnO nanorods, and Zn 2+ ions on saltwater organisms including a producer (alga D. salina), a consumer (crustacean A. salina), and a decomposer (bacterium B. cereus). We observed a clear dose-response relationship for all nanostructures with respect to all tested organisms.…”
Section: Toxicity Of Zno Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The photocatalytic properties of ZnO nano rods have also been investigated against marine micro and macro fouling organisms in laboratory, 143 mesocosm 144 , and field experiments. 145 Photocatalytic compounds such as TiO 2 , ZnO can be nanostructured at low cost and the results they have shown for water purification are promising, leading to prospective applications to disinfect water in homes, as well as in small and large industries. However, the bandgap of these semiconductors pushes their light absorption range in the UV light band, so they can only be activated by a high-energy UV source, whereas the power distribution of the solar spectrum is split between 46% visible light, 47% infrared radiation, and only 7% UV light.…”
Section: •-mentioning
confidence: 99%